First to "Read" the News: News Analytics and Algorithmic Trading. (21st August 2019) - von Beschwitz, Bastian; Keim, Donald B; Massa, Massimo
Abstract: Exploiting a unique identification strategy based on inaccurate news analytics, we document an effect of news analytics on the market independent of the informational content of the news. We show that news analytics speed up the stock price and trading volume response to articles, but reduce liquidity. Inaccurate news analytics lead to small price distortions that are corrected quickly. The market impact of news analytics is greatest for press releases, as news analytics exhibit a particular skill in "seeing through" the positive spin of press releases. Furthermore, we provide evidence that high-frequency traders rely on the information from news analytics for directional trading on company-specific news. Received: May 17, 2018; Editorial decision: June 14, 2019 by Editor: Thierry Foucault. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.